Effect of Nano fertilizer On pea) Pisum sativum. L(growth and productivity. - جنان يوسف عثمان, (Latakia University Journal -Biological Sciences Series, 2022)
The experiment was carried out in Tishreen University garden nursery during 2020-2021 in sandy loam soil, to determine the effect of Nano fertilizer on pea Pisum sativum.var Oterlo growth and productivity, The study included three treatments ( Dima Complex Crystal, Diamond) Of Liquid Nano fertilizer in addition to control, in completely randomized design, with three replications. The results using that treatment of Nano fertilizer significantly improved vegetative growth (plant height, number of leaves, fresh weight) and yield (number of pods per plant, number of seeds per pod, pod weight, plant yield and total yield) of pea compared to control. Crystal compound recorded the highest values for plant height 118 cm, number of leaves 75 leaf/plant, fresh weight 372 g/plant, number of pods 44.7, number of seeds 9, plant yield 455.5 g and total yield 6.5 ton/1000m2 compared to the control( 87.5 cm, 26 leaf, 130 g.11 pod,5 seeds, 220 g and 3.15 ton /1000m2.